Employment of the body in the therapeutic course of mental illness - Zegai, Amel; Mimouni, Mustapha (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
This study presents itself as a service for reading and producing the "soul-body" relationship in the treatment and not only in the diagnosis of mental illness, through theoretical research and a survey of the reality of the results of the practice of therapeutic mediation in general and therapeutic mediation used for the body in particular, as well as the examination of the practical reality of this type of practice in our institutions Hospitals for mental illness. Where did this exploratory field study start in each of the two mental health hospitals in western Algeria، "Oran, Tiaret", in preparation for the baseline study that was conducted through research interviews with a sample of mental health professionals in the institutional setting, where it was confirmed the existence of expressive, therapeutic analytical models, For the body in psychiatric symptoms of cases on the one hand، and in how to provide them with preventive or therapeutic treatment on the other hand. As the expression of the pathology of the soul is done by the body, where its therapeutic function resides in this mediation, which we deduce in its study through the functional modeling of symptomatic pathological manifestations expressing the disorder of each of the main biological functions internal body "sleep, food and sex" which on a psychological basis and the external functions of the body، "the symptomatic demonstration of the body", expressing the functional modeling of the soul and its states in its narcissistic and / or relational struggles. Where the research hypotheses were discussed on the basis of the quantitative and qualitative analysis of the previous results، which we formulated according to the need to follow the therapeutic course of mental illness, i.e. therapeutic demand up to diagnosis through therapeutic monitoring and prevention, this is what led us to conclude in the field that using the body by Mental health professionals are of the utmost importance, appearing first in the result of the therapeutic demand doubled "traditional/ medical", and in the result of a transverse analysis of the cases which reflects an explicit expression of mental illness by the body on the other hand, and in the result of '' a satisfactory longitudinal analysis of cases with precedents in which one was recorded images of physical "auto/ hetero" attacks in third, and following the summaries Unsuccessful states of preventive and therapeutic programs in fourth. what has been institutionally revealed as the lack of activation for therapeutic mediation due to a lack of material capacities and specialized training for professionals in the sector in this field in general or in the field of therapeutic mediation of the body Above all, this is what prompts us to recommend the need to activate and support its specialized training، as well as the need for a therapeutic psychological reading for the body and its manifestation before it reads only a diagnosis. or pharmacotherapeutic as a reading in which there is a shortcut for the human soul.